Pharmacotherapeutic strategies for treating binge eating disorder. Evidence from clinical trials and implications for clinical practice. (13th April 2019) - Amodeo, Giovanni; Cuomo, Alessandro; Bolognesi, Simone; Goracci, Arianna; Trusso, Maria A; Piccinni, Armando; Neal, Stephen M; Baldini, Irene; Federico, Eugenio; Taddeucci, Costanza; Fagiolini, Andrea
ABSTRACT: Introduction : Binge eating disorder (BED) is the most common eating disorder and was newly recognized in 2013 in the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). BED is frequently associated with obesity and the metabolic syndrome, as well as with other psychiatric diseases, such as mood (49%), anxiety (41%), and substance use (22%) disorders. BED is highly prevalent and carries a high burden of mental and physical illness and disability. However, BED is frequently under-recognized and under-treated. Areas covered : This paper reviews the main pharmacological treatments for BED and provides an expert opinion based on the available evidence and on the authors' clinical experience with patients affected by BED. Expert opinion : Several medications have proven to be effective for the treatment of BED, including Lisdexamfetamine (LDX), topiramate as well as anti-anxiety and antidepressant medications. To date, LDX is the only FDA approved medication for BED. Consequently, as a general rule, the use of an FDA approved medication should always be preferred. However, when in the presence of concomitant psychiatric conditions such as anxiety or depression, other medications that have proven efficacy in those comorbid conditions can be used and may contextually provide a benefit for BED.